Es streite, wer kann!: ein neuer Rekonstruktions- und Interpretationversuch für das sumerische Schulstreitgespräch ‚Dialog 1‘ - Matuszak, Jana (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2019)
On the basis of the recent edition of Dialogue 1 by J. C. Johnson and M. J. Geller (2015), this article offers a revised text reconstruction as well as a differing interpretation of the text and its protagonists. The interpretation of Dialogue 1 as a verbal contest between two schoolboys of rather unequal rhetorical proficiency is based on a rhetorical analysis of the dialogue and a more systematic contextualisation within the corpus of Sumerian literary disputations and related compositions.